More Mobile : portable architecture for today - Siegal, Jennifer; Stewart, Jude; Mitchell, William J. (New York : Princeton Architectural Press, 2008)
"The allure of mobile, portable architecture is worldwide and centuries old. From the desert tents of the Bedouin to the silvery capsules of the Airstream trailer, mobile architecture has inspired designers with its singular characteristics of lightness, transience, and practicality. In More Mobile, Jennifer Siegal explores the ever-growing range of possibilities of portable, demountable structures. From serious Refuge Wear to the playful Furnicycle and the practical Kunsthallen, More Mobile explores the methods and finished work of the most exciting contemporary designers working in this field and presents today's most dynamic, active mobile structures with beautiful color images, detailed drawings,and insightful texts."
Studio-Orta -- Dré Wapenaar -- Andrea Zittel -- Andrew Maynard -- Andreas Vogler -- Horden Cherry Lee Architects -- N55 -- Atelier Bow-Wow -- Mark Fisher Studio -- MMW -- LOT-EK -- Offi1e of Mobile Design.
boek